Preservation of sugarcane silage with urea and calcium oxide: performance and metabolic efficiency of dairy cows - Martins, Susi C. S. G.; Carvalho, Gleidson G. P.; Pires, Aureliano J. V.; Leite, Laudí C.; Lago-Novais, Daiane; Oliveira, Ronaldo L.; Cirne, Luis G. A.; Carvalho, Bruna M. A. (Revista Colombiana de Ciencias Pecuarias, 2021)
Background: Inclusion of urea and calcium oxide (CaO) during sugarcane ensilage has been hypothesized to improve dairy cow performance. Objective: To evaluate the use of urea and calcium oxide as additives to preserve sugarcane silage quality and determine whether they improve dairy cow performance and metabolic efficiency. Methods: Four diets were used: sugarcane silage without additive (SS), sugarcane silage with 10 g/kg urea (SU), sugarcane silage with 5 g/kg urea + 5 g/kg CaO (SUC), and sugarcane silage with 10 g/kg CaO (SC). Eight crossbred cows at approximately 100 days of lactation were distributed in two 4x4 Latin squares, and their diets were formulated to reach an average milk production of 15 kg/day. Results: Dry matter, non-fibrous carbohydrates, organic matter, total carbohydrates, and total digestible nutrient intake were the highest (p<0.05) for the cows fed SC. Urinary excretion of nitrogen was higher (p<0.05) for cows fed diets based on SUC than those fed diets with SC. Milk urea nitrogen content was the highest (p<0.05) in animals fed SU diets. Nitrogen balance was positive in all treatments; however, the microbial protein synthesis was low for all diets. Conclusions: The diet with SU showed the highest nitrogen loss through the milk. Among the evaluated silages, those with SC and SUC are recommended to promote a high intake of nutritional components.